Effect of esketamine on postoperative pain relief and depressive status in patients with traumatic fractures - Liu, Zhongyu; Xu, Jinhui; Zhang, Mingsheng; Zhou, Tao (Frontiers in Medicine, 2025)
ObjectiveTo investigate the effects of different doses of esketamine combined with sufentanil on postoperative pain relief and depressive states in patients with traumatic fractures.MethodsThis prospective, randomized, triple-blind, placebo-controlled trial (registered at the Chinese Clinical Trial Registry, Identifier: ChiCTR2100054238) enrolled 225 patients with traumatic lower limb fractures (ASA I-III, aged 18–64) at Jiangxi Provincial People's Hospital between September 2021 and June 2024. Patients were randomly allocated to three groups (n = 75 each). All received a standard postoperative analgesic pump (sufentanil 2 μg/kg + tropisetron 10 mg in 100 ml saline, 1.5 ml/h basal rate, 2 ml PCA bolus, 20 min lockout). Concurrently, they received a 24-h continuous infusion via a separate pump: Group L (low-dose) received esketamine 0.5 mg/kg in 48 ml saline (2 ml/h); Group H (high-dose) received esketamine 0.75 mg/kg in 48 ml saline (2 ml/h); Group C (control) received 48 ml saline (2 ml/h). Primary outcomes were Hamilton Depression Rating Scale (HAMD) scores (assessed preoperatively, and on postoperative days 1, 3, 7) and total sufentanil consumption. Secondary outcomes included Visual Analog Scale (VAS) pain scores, PCA compressions, serum BDNF/IL-6 levels, and adverse events.ResultsBoth esketamine groups (L and H) demonstrated significantly lower HAMD scores on postoperative days 1 and 3 compared to group C (all P < 0.05), with group H showing a greater reduction than group L on day 3 (P < 0.05). Postoperative sufentanil consumption and PCA compressions were significantly reduced in groups L and H vs. C (P < 0.05). Group H also had significantly fewer PCA compressions than group L (P < 0.05). The VAS score was significantly lower in group H than in group C at 12 h post-surgery (P < 0.05). The incidence of postoperative nausea/vomiting was significantly lower in groups L and H compared to group C (P < 0.05).ConclusionContinuous postoperative infusion of esketamine (0.5–0.75 mg/kg over 24 h) in patients with traumatic lower limb fractures effectively alleviates postoperative depressive symptoms, provides opioid-sparing analgesia, reduces opioid-related adverse effects like nausea and vomiting, and is associated with increased BDNF and decreased IL-6 levels.